Growth Of Fluorine Doped Zinc Oxide Nanostructures For Ultra-Violet Photodetector Using Modified Chemical Bath-Hydrothermal Method - Aminu, Muhammad (2022)
The main aim of this research work was the use of modified chemical bath- hydrothermal method for the synthesis of undoped and fluorine doped zinc oxide (FZnO) for ultra-violet (UV) photodetector (PD) application. The effect of fluorine (F) concentration in ZnO properties was investigated on Si substrate, which resulted in enhancement of the crystal quality, optical and electrical properties of ZnO at low F concentration. Subsequently, UV metal-semiconductor-metal (MSM) PD was fabricated based on the undoped ZnO and optimized FZnO. When compared to an undoped ZnO device, the photodetection properties of the optimized FZnO device were enhanced appreciably using the UV-light of 395 nm. The value of photocurrent, responsivity, sensitivity, detectivity, rise time and fall time of the undoped ZnO device were 3.61 μA, 0.22 A/W, 9.7 x103%, 2.2 x1019 Jones, 1.9 s and 1.7 s, respectively. The parameters for the FZnO device on the other hand, were increased to 10.52 μA, 0.66 A/W, 1.1x105%, 1.3x1010 Jones, 90 ms and 110 ms, respectively. Hence, FZnO nanorod (NRs) synthesized using modified hydrothermal method revealed outstanding findings which could be extremely beneficial in the design and manufacture of inexpensive UV MSM PD devices for a variety of optoelectronic applications. In addition,